A flexible paper based strain sensors drawn by pencil for low-cost pressure sensing applications - Mat Nawi, Mohd Norzaidi; Ho Lau, Jim Tze (Bulletin of Electrical Engineering and Informatics, 2024)
Paper-based strain sensors, offering a cost-effective and environmentally friendly solution, are in demand for pressure sensing applications. Here, we present a simple sensor design comprising a piece of paper, a graphite pencil, and a copper plate. The proposed fabrication process is simple and eco-friendly. Beyond design and fabrication, our study explores the performance of paper-based sensors in effectively measuring and monitoring pressure changes induced by varying deflection angles. Our findings show that as the deflection angle increases, the sensor exhibits a proportional increase in the relative change in resistance. Furthermore, the practical applicability of the fabricated sensor is demonstrated through real-world testing on a human finger, considering different positions. In essence, our research positions paper-based strain sensors as a promising and practical choice for affordable, eco-friendly, and responsive pressure sensing.